2020
DOI: 10.1016/j.foodcont.2020.107310
|View full text |Cite
|
Sign up to set email alerts
|

A 20-year analysis of reported food fraud in the global beef supply chain

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Reports on RASFF include the type and date of notification, the reason for notification, the hazard(s), the nature of the product involved, the country of notification, and the country of origin (EFSA, 2010;Djekic, Jankovic & Rajkovic, 2017). Although this is a database used to record and food safety incidents, it has been used as a horizon scanning tool in multiple academic publications (Tähkäpää et al, 2015;Marvin et al, 2016;Robson et al, 2020).…”
Section: Large Scale Operatorsmentioning
confidence: 99%
“…Reports on RASFF include the type and date of notification, the reason for notification, the hazard(s), the nature of the product involved, the country of notification, and the country of origin (EFSA, 2010;Djekic, Jankovic & Rajkovic, 2017). Although this is a database used to record and food safety incidents, it has been used as a horizon scanning tool in multiple academic publications (Tähkäpää et al, 2015;Marvin et al, 2016;Robson et al, 2020).…”
Section: Large Scale Operatorsmentioning
confidence: 99%
“…Although it is difficult to quantify the impact on the whole food supply chain, Spielman (2020) [2] estimated the impact of food fraud on the food industry to be in excess of $50 billion annually. Food and drink categories most commonly affected by fraud include dairy products [3,4], meat products [3,5], seafood [3,6], alcohol products [3,6], and fats and oils [6,7]. The type of adulterants used in dairy products includes nitrogen sources (e.g., ammonium salts, melamine, urea, and non-dairy proteins) [8,9] to mask the reduction of dairy protein content caused by dilution.…”
Section: Introductionmentioning
confidence: 99%
“…This increased interest in food authenticity may also be explained by the numerous food scandals over the last few years (e.g., horsemeat scandal in 2013 and rotten meat from Brazil in 2017) and the increased consumer awareness about the impacts of food fraud in terms of illegal economic gain, as well as negative effects on the public health and the environment. Nonetheless, several recent studies have indicated that fraud or mislabeling is still a widespread practice, especially in food products of animal origin, which are often considered among the most frequently adulterated foods [ 3 , 4 , 5 , 6 ]. Market globalization and increases in international trade, driven by fewer obstacles to the export and import of food, a complex food production chain, and the complex nature of food products of animal origin, the huge variety of these products, as well as the emergence of tricky and more sophisticated forms of fraud are some of the reasons that could explain this rise in food fraud and why detection and prevention are challenging tasks [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%